A Double Closed-Loop Process for Nanoparticle Synthesis via Aerosol Mixing and Venturi Jet Scrubbing - Bruno Fabiano; Marco Salerno; Marco Vocciante; Omar Soda; Andrea Pietro Reverberi (Applied Sciences)
Inorganic nanoparticles (NPs) have been synthesised via mixing and coalescence of droplets containing precursors and entrained by gaseous streams. The droplets have been generated by ultrasonic aerosolisation of two different liquid phases, each containing the respective reagent. The as-produced NPs are trapped by mixing with a liquid phase in a Venturi nozzle, acting simultaneously as a collector and concentrator of the solid nanosized phase produced. Commercial electrically powered ultrasonic aerosolising devices have been adapted to atomise salt solutions characterised by high electrical conductivity. This process allowed the synthesis of calcium carbonate NPs with an average diameter in the range of (34–52) nm, according to the concentration of precursors in the aerosolised phases. This closed-loop method of synthesis, where neither capping agents were used nor demanding operating conditions were adopted, can represent a safe and viable eco-friendly technique for NP production free of undesirable compounds, as required for pharmaceutical preparations and theranostic uses.